2021
DOI: 10.1021/acs.jmedchem.1c00567
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of First-in-Class Dual PARP and EZH2 Inhibitors for Triple-Negative Breast Cancer with Wild-Type BRCA

Abstract: PARP inhibitors have highly significant effects on BRCA mutant cells, allowing targeted therapy of triple-negative breast cancer (TNBC). However, some TBNC patients lack BRCA mutations. Recent studies have shown that EZH2 inhibitors can increase the sensitivity of wild-type BRCA cells to PARP inhibitors. We designed a series of dual PARP and EZH2 inhibitors, and the most promising compound, 5a, showed good inhibitory activity against PARP-1 and EZH2 and good inhibitory effects on MDA-MB-231 (IC 50 = 2.63 μM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Therefore, Wang et al designed a series of dual inhibitors of PARP1 and EZH2 (Figure ). These researchers replaced the benzylmorpholine structure of tazemetostat with a linker and combined it with the pharmacophore of olaparib. , Structure–activity relationship (SAR) studies showed that the introduction of methyl ( 17b ) at the ortho position of the amide enhanced the activity, and the activity of compounds with an electron-withdrawing group ( 17c ) on the benzene ring was lower than that of compounds with an electron-donating group ( 17d ). The replacement of the amino group on the benzene ring by an amide structure yielded 17e .…”
Section: Tazemetostat and Ezh2 Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…Therefore, Wang et al designed a series of dual inhibitors of PARP1 and EZH2 (Figure ). These researchers replaced the benzylmorpholine structure of tazemetostat with a linker and combined it with the pharmacophore of olaparib. , Structure–activity relationship (SAR) studies showed that the introduction of methyl ( 17b ) at the ortho position of the amide enhanced the activity, and the activity of compounds with an electron-withdrawing group ( 17c ) on the benzene ring was lower than that of compounds with an electron-donating group ( 17d ). The replacement of the amino group on the benzene ring by an amide structure yielded 17e .…”
Section: Tazemetostat and Ezh2 Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…In the work reported by Wang, et al, they used compound 1 and tazemetostat as the starting point to design the dual PARP and EZH2 inhibitors (73). Analysis of the complex of tazemetostat-EZH2 revealed that the benzylmorpholine moiety oriented to the solvent and can tolerate structural modification.…”
Section: Parp/ezh2 Dual Targeting Inhibitorsmentioning
confidence: 99%
“…Some BRD4 or PARP-related dual-targeted inhibitors have been shown to have good effects on malignant cancers, including pancreatic cancer and breast cancer. Based on our previous findings, simultaneous inhibition of BRD4 and PARP1 by ADTL-BPI1901 ( 11 ) significantly triggered the death of cancer cells . Nonetheless, further development of dual-targeted inhibitors is necessary due to the relatively weak activity of ADTL-BPI1901 on PARP1 and its unsatisfactory bioavailability.…”
Section: Introductionmentioning
confidence: 97%